إشكالیة تدبیر النفایات الصلبة بمدینة فاس : مقاربة جغرافية - الصنهاجي غزلان (جامعة سيدي محمد بن عبد الله، كلية الآداب و العلوم الإنسانية - ظهر المهراز، فاس, 2020)
The rise of the problem of solid waste and their management coincided with the demographic growth witnessed by most of the Moroccan cities since the mid 20th century. This rapid growth of population followed a transition in thesocial and economic development that took Morocco into a new shift characterized by a remarkable instability among the cities. The latter have grown without a governed planning which lead to a number of environmental problems including the issue of solid waste management. For instance, the city of Fes did never face any challenge concerning the management of solid waste especially after independence. However, this given fact would change with the beginning of the 80s regarding to various factors headed by over population, industrialization and life style changes among the Moroccan families. These factors have led to the increase in the number of solid wastes which have turned the streets and the neighborhoods of the city into black spots which threaten the population and the environment. Despite the fact that the urban community has entrusted foreign companies to take charge over the management of solid wastes, this experience was doomed to failure. In this context, the present thesis examines the management of solid wastes in the city of Fes through a geographical approach that has started from scrutinizing the condition of this sector. To approach this subject, we relied on an analytical and descriptive method analysis alongside other tools such as bibliography and fieldwork and maps. All these tools enabled us to reach out several results and conclusions.
Keywords: جغرافیا; Interface, Ressources, Sociétés et Dynamiques Territoriales